Solve for x 2.6(x-0.8)=9.3-x

Math
2.6(x-0.8)=9.3-x
Simplify 2.6(x-0.8).
Tap for more steps…
Apply the distributive property.
2.6x+2.6⋅-0.8=9.3-x
Multiply 2.6 by -0.8.
2.6x-2.08=9.3-x
2.6x-2.08=9.3-x
Move all terms containing x to the left side of the equation.
Tap for more steps…
Add x to both sides of the equation.
2.6x-2.08+x=9.3
Add 2.6x and x.
3.6x-2.08=9.3
3.6x-2.08=9.3
Move all terms not containing x to the right side of the equation.
Tap for more steps…
Add 2.08 to both sides of the equation.
3.6x=9.3+2.08
Add 9.3 and 2.08.
3.6x=11.38
3.6x=11.38
Divide each term by 3.6 and simplify.
Tap for more steps…
Divide each term in 3.6x=11.38 by 3.6.
3.6×3.6=11.383.6
Cancel the common factor of 3.6.
x=11.383.6
Divide 11.38 by 3.6.
x=3.161‾
x=3.161‾
Solve for x 2.6(x-0.8)=9.3-x

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top